A MULTIDISCIPLINARY APPROACH TO A CASE OF CONDYLOMA ACUMINATA IN AN ADOLESCENT FEMALE FOLLOWING SEXUAL ABUSE – CASE REPORT - Sakinah, Dyah Ayu; Setyowatie, Lita (Journal of Psychiatry Psychology and Behavioral Research, 2026)
Introduction: Condyloma acuminata (CA) is a sexually transmitted disease caused by human papillomavirus (HPV) and typically presents as exophytic, verrucous lesions on moist mucocutaneous surfaces, including the anogenital region. The infection is highly transmissible and may occur as solitary or multiple lesions of varying sizes. In pediatric and adolescent populations, the identification of sexually transmitted infections may represent an early clinical indicator of sexual abuse. The aim of this report to highlight the role of a multidisciplinary approach in comprehensive patient management. Methods: A 15-year-old female presented with genital warty lesions. Dermatovenereological examination revealed multiple skin-colored verrucous papules involving the labia majora and minora, without tenderness or bleeding. Detailed anamnesis obtained from the patient and her caregiver disclosed a history of sexual abuse. The clinical diagnosis was confirmed by histopathological examination of biopsied lesions. Results: The patient was diagnosed with condyloma acuminata associated with HPV infection in the context of sexual abuse. Management involved collaboration among dermatovenereologists, pediatricians, psychiatrists, and pediatric surgeons to address both medical conditions and psychological trauma. Discuss: Management of this patient required a multidisciplinary approach involving pediatrics for underlying aplastic anemia, dermatovenereology for genital warts, psychiatry for psychological trauma, and pediatric surgery for definitive lesion management. Such coordinated care was essential to address both the medical and psychosocial complexities associated with condyloma acuminata following adolescent sexual abuse. Conclusion: The presence of condyloma acuminata in children or adolescents should prompt careful evaluation for possible sexual abuse. Early diagnosis and coordinated multidisciplinary management are crucial to achieving optimal medical treatment and psychological recovery.  Keywords: pseudobulbar affect, stroke, antidepressant.